Evaluasi Pengaruh Tegangan Kerja Generator terhadap Kualitas Tegangan Jaringan pada PT.PLN (Persero) Area Luwuk - Herman Nawir; Muhammad Yusuf Yunus; Ibnu Amir (Politeknik Negeri Ujung Pandang, 2021)
One of the service quality parameters is that the voltage supplied to consumers is always at the set value, which is 20 kV for medium voltage and 380/220 Volt for low voltage, many factors can affect the magnitude of the voltage starting when the voltage is generated by the generator, the process distribution to consumers by using a conductor and the amount of load that is on the feeder. This study aims to determine how much influence the generator output voltage has on changes in voltage in the medium voltage network and how much voltage drop occurs at the JTM until it reaches the consumer. The results show that the generator output voltage will affect the base voltage, the greater the generator output voltage, the greater the base voltage and operating voltage of the system. The voltage drop along the industrial feeder before the generator voltage is increased is 281,856 Volts or if it is used as a percentage of 1.441% but when the generator output voltage is increased the voltage drop in the industrial feeder decreases by 277.016 Volts or if it is used as a percentage of 1.392%.